Location Context Awareness System for Specific Positioning Based on Received Signal Strength for Android Platform System - Khamla NonAlinsavath; Vimontha Khieovongphachanh; Phouthong Southisombath; Aditep Chaisang; Sanouphab Phomkeona; Khanthanou Luangxaysana; Supakorn Suwan; Sathaporn Promwong (My University, 2023)
In the current era of seamless integration across various contexts, the ability to track mobility both indoors and outdoors has become crucial for many individuals. Tracking the path of mobility from the initial point to the final destination is essential in numerous aspects of human life. This study presents a location-aware computing application that facilitates the smooth integration of indoor and outdoor environments by combining both requirements within a smart device-based system, without any barriers. The proposed work utilizes the Global Positioning System (GPS) and the Global System for Mobile Communications (GSM) to measure external conditions, while Wi-Fi Fingerprinting (Wi-Fi) is employed to accurately determine the user's indoor locations using received signal strength indicator. The integration of indoor and outdoor technologies ensures seamless user mobility. As users transition between different conditions, the system effectively addresses the complexities that arise between indoor and outdoor locations. The transition time between indoor and outdoor is less than 5 seconds, with seamless switching occurring in the overlapped areas. In our experiments conducted within a campus building, the system achieved a remarkable accuracy of 98.4% for outdoor-to-indoor movement and 97.7% for the reverse movement. Furthermore, the seamless location system offers significant benefits to users, including the discovery of new system features, access to directional maps, and guidance along pathways from their current locations.
Keywords: Indoor and Outdoor Localization Technologies; Human Mobility and Location-Based Analysis; Context-Aware Activity Recognition Systems